Propects for regional integration in Central Asia: the case of eurasec - Moldosanov, Janybek (My University, 2006)
Orta Asya ülkeleri arasındaki ekonomik işbirliği, hem bu ülkelerin ekonomik ve sosyal gelişmelerininnin doğal bir sonucu, hem bu gelişme için olmazsa olmaz şartlarındandır. Bu ülkelerin coğrafik açıdan birbirlerine olan yakınlığı, ortak tarihsel, kültürel ve sosyal bağları, ve bunun dışında geçmişte Sovyetler Birliği çatısı altında kurulan ortak altyapı, ve ekonomik bağları ekonomi ve diğer alanlarda işbirliğini kaçınılmaz yapan sebeplerdendir. Sovyetler birliğinin dağılması, ve Orta Asya ülkelerinin bağımsızlıklarını elde etmeleri sonucunda kopmuş olan bağlar şimdilerde tekrar dizeltilmeye çalışılıyor. Hem Rusya, hem Orta Asya ülkelerinin yürütmüş oldukları politika ekonomilerin yakınlaşmasına yöneliktir. İşbirliğinin EURASEC (Avrasya Ekonomik Topluluğu) çerçevesi içinde gelişmesi ve derinleşmesi üye ülkelerin ekonomik ve sosyal gelişmesini sağlayabilir, ve dahası, gelecekte dünya arenasında yeni bir oluşumun ortaya çıkmasının temeli olabilir.

Economic cooperation among the Central Asian countries can be viewed both as natural outcome of and as prerequisite for their economic and social development. It is a natural outcome partly because of their geographical proximity. Economic cooperation is also a necessity as each of the countries individually has a rather small market. More importantly, these countries used to be parts of the big economic complex of the former Soviet Union. The infrastructure of the Soviet Union was a common one. In many respects, cooperational ties have not been lost, or may be restored, and close contacts between people have been preserved. Moreover, there exist common cultural and social traditions. After the break-up of the Soviet Uion, some of the links were severed. However, recently, there have been made some efforts to restore and revitalize economic complementarity among these countries. A course toward mutual economic rapprochement is an official policy of both Russia and the Central Asian countries. Development and deepening of cooperation within the framework of integration association, namely, the EURASEC may provide the social and economic progress of the member states, and moreover may lead to formation of a competitive participant of economic and political activity in the world arena.
Keywords: Ekonomik İlişkiler_Asya, Orta; Ekonomik İşbirliği_Orta Asya